Pembuatan Sistem Informasi Registrasi Dosen dan Jabatan Akademik Dosen dengan Penggunaan Framework Laravel di Lingkungan Perguruan Tinggi secara real time - Hendra Gunawan; Desi Suryani; Sony Susanto (Jurnal Accounting Information System (AIMS), 2023)
To become a teacher at a university, an individual needs to have registration which includes a National Lecturer Identification Number (NIDN), Special Lecturer Identification Number (NIDK) or Educator Serial Number (NUP). After the lecturer has a registration number, the lecturer then takes care of the lecturer academic position (JAD) to indicate the duties, responsibilities, authority and rights of a lecturer. The application process carried out by lecturers faces a number of obstacles such as incomplete documents and lecturers being slow in completing the requirements. The aim of this research is to overcome problems that arise during the process of applying for lecturer registration numbers and lecturer academic positions by creating an information system that can help lecturers. This information system will also be accessed by lecturers to track the status of their submissions and generate automatic reports to leadership. The system development method uses waterfall and the PHP programming language with the Laravel framework. The result of this research is an information system that can assist lecturers in monitoring and checking data on submission of lecturer registration numbers and lecturer academic positions.